Polyprenylated benzophenones with a tricyclo [4.3.1.1(3,8)]undecane skeleton from Clusia obdeltifolia - Cruz,Frederico G. (2004)
The hexane extract of Clusia obdeltifolia trunk yielded three new polyprenylated benzophenones 7beta-H-11-benzoyl-5alpha-hydroxy-6,6,10,10-tetramethyl-1-(3-methyl-2-butenyl)tetracyclo [7.3.1.1(3,11)0(3,7)]tetradecane-2,12,14-trione, 8-benzoyl-4alpha-(1-hydroxy-1-methylethyl)-7,7-dimethyl -1,3-di(3-methyl-2-butenyl)tricyclo[4.3.1.1(3,8) ]undecane-2,9,11-trione and 7alpha-H-1-benzoyl-4-hydroxy-3-(3-hydroxy-3methylbutyl)-6,6,13,13-tetramethyl-11- (3-methyl-2-butenyl)-5 -oxatetracyclo[7.3.1.0(3,7)0(4,11) ]tridecane-2,12-dione along with two known polyprenylated benzophenones, sampsonione B and sampsonione G. These benzophenones exhibited a complex tricyclo [4.3.1.1(3,8)]undecane skeleton and their structures were determined from spectral data and comparison with those of previously reported compounds.